Cloning, Overexpression, and Purification of PhoR CytoplasmicDomain Protein from Mycobacterium tuberculosis strain H37Rv - OKTIRA ROKA AJI; DYSHELLY NURKARTIKA PASCAPURNAMA; FENRYCO PRATAMA; IHSANAWATI IHSANAWATI; MAELITA RAMDHANI MOEIS; ERNAWATI ARIFIN GIRI-RACHMAN (Indonesian Society for microbiology, 2014)
Tuberculosis still becomesa major health problem in the world. This infectious disease is caused by Mycobacterium tuberculosis (Mtb). Novel anti-tubercular drug is urgently needed to counter multidrug resistant cases and Mtb's spread. The cytoplasmic domain of PhoR histidine kinase, a part of the two-component system PhoR-PhoP in Mtb, is one of the potential candidates for anti-tubercular drug target.Three dimensional protein of drug target is needed to screen potential drug candidate using rational drug design approaches. Previous studies have successfully characterized and isolated putative cytoplasmic domain of PhoR (CytoPhoR) from Mtb strain H37Rv. This study aimed to clone, overexpress and purify of CytoPhoR protein. CytoPhoR was fused with thioredoxin protein in expression vector pET32b and overexpressed in Escherichia coli (E.coli)BL21 (DE3) as soluble fraction by inductionÂ 1 mM IPTG. Purification of his-tagged CytoPhoR was carried out using IMAC Ni-NTA Agarose his-tag affinity column. SDS-PAGE analysis showed that another protein was co-purified ( 35 kDa) along with the CytoPhoR protein. Subsequent protein purification using DEAE-ion exchange column generate a strong single band of 37 kDa on SDSâ€“PAGE which is indicated as CytoPhoR protein. The purified CytoPhoR protein was successfully obtained and can be used for further analysis on determining three dimensional structure of CytoPhoR protein.